Comparison of Perioperative Outcomes Between Laparoscopic and Open Approach for Pancreatoduodenectomy: The PADULAP Randomized Controlled Trial. Issue 5 (November 2018) - Poves, Ignasi; Burdío, Fernando; Morató, Olga; Iglesias, Mar; Radosevic, Aleksander; Ilzarbe, Lucas; Visa, Laura; Grande, Luís
Abstract : Objective: To compare perioperative outcomes of pancreatoduodenectomy (PD) performed through the laparoscopic route or by open surgery. Summary Background Data: Laparoscopic PD is being progressively performed in selected patients. Methods: An open-label single-center RCT was conducted between February 2013 and September 2017. The primary endpoint was the length of hospital stay (LOS). Secondary endpoints were operative time, transfusion requirements, specific pancreatic complications (pancreatic or biliary fistula, pancreatic hemorrhage, and delayed gastric emptying), Clavien–Dindo grade ≥ 3 complications, comprehensive complication index (CCI) score, poor quality outcome (PQO), and the quality of pathologic resection. Analyses were performed on an intention to treat basis. Results: Of 86 patients assessed for PD, 66 were randomized (34 laparoscopic approach, 32 open surgery). Conversion to an open procedure was needed in 8 (23.5%) patients. Laparoscopic versus open PD was associated with a significantly shorter LOS (median 13.5 vs. 17 d; P = 0.024) and longer median operative time (486 vs. 365 min; P = 0.0001). The laparoscopic approach was associated with significantly better outcomes regarding Clavien–Dindo grade ≥ 3 complications (5 vs. 11 patients; P = 0.04), CCI score (20.6 vs. 29.6; P = 0.038), and PQO (10 vs. 14 patients; P = 0.041). No significant differences in transfusion requirements, pancreas-specific complications, the number of lymph nodes retrieved, and resection margins between the two approaches were found. Conclusions: Laparoscopic PD versus open surgery is associated with a shorter LOS and a more favorable postoperative course while maintaining oncological standards of a curative-intent surgical resection. Trial registry: ISRCTN93168938.